Hypoglossal Nerve Stimulation: Outcomes in Veterans with Obstructive Sleep Apnea and Common Comorbid Post‐traumatic Stress Disorder. (9th December 2020) - Dhanda Patil, Reena; Sarber, Kathleen M.; Epperson, Madison V.; Tabangin, Meredith; Altaye, Mekibib; Mesa, Franklin; Ishman, Stacey L.
Abstract : Objectives/Hypothesis: Veterans have an increasing prevalence of obstructive sleep apnea (OSA) and high levels of intolerance to positive airway pressure (PAP). The hypoglossal nerve stimulator (HNS) is a promising alternative surgical treatment for OSA in these patients, many of whom suffer from mental health conditions such as post‐traumatic stress disorder (PTSD) that may negatively affect their ability to use PAP. Our aims were: 1) to assess postoperative changes in OSA severity and sleepiness in a veteran only population after HNS; 2) to compare postoperative changes in OSA severity, sleepiness and HNS adherence between veterans with and without PTSD; and 3) to compare HNS adherence in our population to HNS adherence in the current literature as well as published PAP adherence data. Study Design: Retrospective and prospective case series. Methods: Clinical data on consecutive patients undergoing HNS in a Veterans Affairs hospital were examined for demographic data as well as medical, sleep, and mental health comorbidities. The overall cohort as well as subsets of patients with and without PTSD were examined for postoperative changes in OSA severity (apnea hypopnea index [AHI], lowest oxygen saturation (LSAT]), and sleepiness (Epworth sleepiness scale [ESS]), as well as for device adherence. PTSD and depression symptomatology were measured using the PTSD Checklist 5 (PCL‐5) and Patient Health Questionnaire 9 (PHQ‐9). Results: Forty‐six veterans were included. Forty‐four patients were male (95.6%), 45 were white (97.8%), and the mean age was 61.3 years. Twenty‐six patients met PCL‐5 criteria for PTSD and 17 did not. OSA severity and sleepiness improved significantly in the overall cohort after HNS; median (IQR) AHI decreased from 39.2 (24.0, 63.0) to 7.4 (1.2, 20.8) events/hour ( P  < .0001), mean LSAT increased from 81% to 88% ( P  < .0001) and mean ESS decreased from 10.9 to 6.7 ( P  < .0001). These improvements were similar between patients with and without PTSD ( P = .434–.918). Overall device adherence was 6.1 hours/night for the overall cohort and was not significantly different between patients with and without PTSD ( P = .992). Conclusions: HNS is an efficacious therapy in a veteran population, providing patients with significant improvements in OSA severity and sleepiness. Veterans with and without PTSD benefited similarly from HNS when comparing improvements in sleep apnea severity and sleepiness as well as device usage. Adherence was similar to previously published HNS adherence data and better than PAP adherence reported in the literature. Level of Evidence: 4 Laryngoscope, 131:S1–S11, 2021